1998
DOI: 10.1016/s0014-5793(98)00680-2
|View full text |Cite
|
Sign up to set email alerts
|

Conformational preferences in the Ser133‐phosphorylated and non‐phosphorylated forms of the kinase inducible transactivation domain of CREB

Abstract: Phosphorylation of SerIQQ within the kinase inducible transactivation domain (KID) of the transcription factor CREB potentiates interaction with the KIX domain of coactivator CBP. Heteronuclear NMR spectroscopic analyses reveal that the KID domain is largely unstructured except for residues that comprise the K KA helix in the pKID-KIX complex, which populate helical conformations to a significant extent ( s 50%). The helical content in the K KB region is very small in the non-phosphorylated form (V10%) althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
166
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(196 citation statements)
references
References 33 publications
27
166
1
2
Order By: Relevance
“…The FEL of the single-chain pKID system showed that the helical propensity for the αB region is considerably smaller than that of the αA region, which is in agreement with experimental results (Radhakrishnan et al 1998). In the pKID-KIX coexisting system, FEL illustrated a number of semi-stable bound forms, including the native-like complex conformation.…”
Section: Applications Of Ttp-mcmd To Interactions Between Intrinsicalsupporting
confidence: 90%
“…The FEL of the single-chain pKID system showed that the helical propensity for the αB region is considerably smaller than that of the αA region, which is in agreement with experimental results (Radhakrishnan et al 1998). In the pKID-KIX coexisting system, FEL illustrated a number of semi-stable bound forms, including the native-like complex conformation.…”
Section: Applications Of Ttp-mcmd To Interactions Between Intrinsicalsupporting
confidence: 90%
“…NMR signals of residues around Ser-133 are shifted by the Ser-133-phosphorylation ( Figure 3b). As in vitro phosphorylation has been previously shown to phosphorylate KID specifically at 17], we conclude that Ser-133 of KID is correctly phosphorylated by PKA in E. coli. pKID produced using the in vivo phosphorylation method binds KIX with identical affinity as pKID produced via in vitro phosphorylation (data not shown).…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 73%
“…1 H-15 N heteronuclear single quantum coherence (HSQC) spectra [16] were measured for all samples. The cross peaks of [ 15 N]-KID were identified based on our previous assignments [17].…”
Section: Preparation Of Phosphorylated Kidmentioning
confidence: 99%
“…An R domain composed predominantly of random coil has an analogy in the kinase-inducible domain (KID) of the cAMP-responsive element-binding protein (CREB). Several structural parameters indicate that KID is unstructured (48)(49)(50)(51). Like R8, serine phosphorylation of KID does not increase structure (48,51).…”
Section: Discussionmentioning
confidence: 96%